Final year grade computation using PHP and Java - Slyvister Max Well Giluk (Universiti Malaysia Perlis, 2008)
Universiti Malausia Perlis (UniMAP) is a distributed university which located in a few different locations in Perlis as Kangar, Kubang Gajah, Automart, Taman Semarak, Taman Muhibbah, and Kg.Wai.The student’s hostel also placed in different location as Kg.Wai, Taman Semarak, Taman Aman, and Wang Ulu. Academic in UniMAP is based on 40% theoretical and 60% practical. Naturally, 4 credit hours for core subject which 3 credit hours is for theoretical and the rest is for lab session. All final year students must take the Final Year Project course (EKT444) as one of the requirement to graduate. Every student will assign to one supervisor. One of the major problem here is there is no online system to record students details and their marks. All works don manually, so it is very important to build up a web system to record data and store it on one database. The lecturer or supervisor will register their students. For the first time registration, lecturer only needs to enter student details such as identity card number student name matrix number and title of the project. At the end of the semester lecturer can edit the student page by adding marks and grade. Students also can view or print their result. If Lecturer or admin forgot their password, there is function to request the forgotten password by email. In this web system there is another few function such as change password and session errors. Users are requiring login to use this web system. One of the important aspect needs more attention is security and prevents duplicate data in database.